2018
DOI: 10.1002/rrq.238
|View full text |Cite
|
Sign up to set email alerts
|

Do Resources Matter? Effects of an In‐Class Library Project on Student Independent Reading Habits in Primary Schools in Rural China

Abstract: It is commonly believed that reading challenges should be addressed early to reduce the likelihood that developmental delays will impact students over the long term. However, students in developing countries often have limited access to reading resources. In this study, the authors used a randomized controlled trial of 11,083 fourth‐ and fifth‐grade students in 120 primary schools in rural China to examine the causal effect of an in‐class library program on student reading outcomes and academic achievement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…Our results showed a small but significant positive effect of the WLR programme on children's reading attitudes and practices. This finding is consistent with an intervention approach in rural China where an in‐class library programme significantly changed fourth‐grade and fifth‐grade students' reading habits (Yi et al, 2018). Nevertheless, providing books alone may not be sufficient.…”
Section: Discussionsupporting
confidence: 85%
“…Our results showed a small but significant positive effect of the WLR programme on children's reading attitudes and practices. This finding is consistent with an intervention approach in rural China where an in‐class library programme significantly changed fourth‐grade and fifth‐grade students' reading habits (Yi et al, 2018). Nevertheless, providing books alone may not be sufficient.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, neither teachers nor parents received any training in supporting the students' reading in this study. It has been found that the intervention impact tends to be smaller for children in the books only condition than for those in the books plus teacher or parental scaffolding condition (Gao et al 2020;Kim and White 2008;Yi et al 2019). Future research may supplement the intervention with training for teachers or parents so that they can scaffold children's reading.…”
Section: Discussionmentioning
confidence: 99%
“…However, these interventions rarely targeted at elementary schoolers in early grades and did not focus on reading skills (e.g., Bai et al 2017;Li et al 2017;Loyalka et al 2013;Mo et al 2013;Yi et al 2015). Some exceptions are evaluations of the effects of book corners on the reading skill development and academic performance of 3rd-to 6th-graders in rural China (Gao et al 2018;Yi et al 2019).…”
Section: Relevant Studies In China and The Present Studymentioning
confidence: 99%
“…According to some previous studies (Petrin et al, 2014;Weiner, 2012;Weiner & Jerome, 2016), although urban, suburban and rural school systems face the same shortages of registered teachers and school professional staff, rural school systems often struggle to recruit due to the remote locations involved and the lack of essential support for teachers' families and teaching strategies. In fact, many teachers are willing to move to regional and rural communities for work (Halsey & Drummond, 2014), but those with families face the same problems for their children, particularly the lack of teaching and learning support (Yi et al, 2018). As most of the participants were single individuals and fresh university graduates, many do not need to consider such matters.…”
Section: Missions and Goals For Development In Regional And Rural Communitiesmentioning
confidence: 99%